ChemInform Abstract: Ligand‐Free, Cu‐ and Fe‐Catalyzed Selective Ring‐Opening Arylations of Benzoxazoles with Aryl Iodides. Issue 42 (September 2016) - He, Yue; Mao, Jincheng; Rong, Guangwei; Yan, Hong; Zhang, Guoqi
Abstract: The copper‐catalyzed reaction of benzoxazoles with aryl iodides leads to 2‐(diarylamino)phenols, whilst the iron‐catalyzed reaction affords 2‐(arylamino)phenols.